Estudio de prefactibilidad para determinar la viabilidad de la Exportación de Mango a Sidney (Australia) Desde Ibagué (Tolima-Colombia) (2022)
The current document is mainly based on investigating the viability on exporting mango from Ibagué (Tolima – Colombia) to the city of Sidney (Australia); taking advantage principally of the per capita incomes that this country owns and the high production that Colombia national territory has, specifically, on Tolima department. All of this, in order to explore new markets abroad with Colombian products.